Anti-trypanosomal Potential of Methanolic Extract of Calotropis gigantea Leaves against Trypanosma evansi and its Cytotoxicity - Shaba, P.; Pandey, N. N.; Sharma, O. P.; Rao, J. R.; Singh, R. K. (International Journal of Bio-resource and Stress Management, 2023)
In an attempt to find anti-trypanosomal extract/compound(s) from medicinal plant for the treatment of trypanosomosis, Calotropis gigantea leaves were extracted with methanol. The obtained extract was screened at concentrations (250-1000 μg ml-1) against Trypanosoma evansi for an in vitro trypanocidal activity on Vero cell line (SIGMA) maintained in Dubecco’s Modified Eagle Medium (DMEM). 500,000 cells ml-1 well-1 was seeded in flat bottom ELISA plates supplemented with 20-40% fetal calf serum (FCS), and incubated at appropriate conditions for more than 12 h. In vitro cytotoxic effects of methanolic plant extract (MPE) of C. gigantea was done on same medium, without FCS, at concentrations (1.56-100 μg ml-1)), and incubated for 72 h. Adhered cells in the plate were stained with a drop of crystal violet in phosphate buffered solution. During in vitro testing, at concentrations of 250-500 μg ml-1, there was immobilization, reduction of average mean trypanosomes count (40.00±0.0 to 13.33±0.67), and complete killing of trypanosomes at 750 μg ml-1 in 9 h of incubation, which was equivalent to diminazine aceturate (Berenil) 50 μg ml-1 (standard drug) at 4 h. In vitro cytotoxic effects such as distortion, swelling, sloughing and death of Vero cells from the bottom of affected wells were observed. MPE of C. gigantea and diminazine aceturate were cytotoxic to Vero cells in all concentrations except at 1.56 and 6.25-1.56 μg ml-1, respectively. MPE of C. gigantea demonstrated presence of trypanocidal compounds.